Job Satisfaction of Special School Teachers - Sathya, A; Arumugam, G. (Journal of Neonatal Surgery, 2025)
The study's primary objectives were to find out the level of job satisfaction of special school teachers, to find out the significant difference between male and female special school teachers in their job satisfaction, to find out the significant difference between rural and urban special school teachers in their job satisfaction, to find out the significant difference among teaching experiences below 5 years, 6 to 10 years and above 10 years’ special school teachers in their job satisfaction, and to find out the significant association between age of special school teachers in their job satisfaction. A survey method was used for the study. A simple random sampling technique was used for selecting 500 special school teachers in Tamil Nadu. The self-made tool Job Satisfaction Scale, was used to collect the data. Descriptive and inferential statistical techniques were used for analysing the data. It was found that the level of job satisfaction of special school teachers is moderate, there is significant difference between male and female special school teachers in their job satisfaction, there is no significant difference between rural and urban special school teachers in their job satisfaction, there is significant difference among teaching experiences below 5 years, 6 to 10 years and above 10 years’ special school teachers in their job satisfaction, and there is significant association between age of special school teachers in their job satisfaction.